Quality of work-life and associated factors among nurses working in Wollega zones public hospitals, West Ethiopia: A cross-sectional study - Getu Mosisa; Muktar Abadiga; Adugna Oluma; Bizuneh Wakuma (International Journal of Africa Nursing Sciences, 2022)
Background: Health care organizations should emphasize their professional quality of work-life to retain committed and qualified employees. Improvement of quality of work-life among health care providers, particularly nurses, positively affects patient outcomes. However, little information is known about the quality of work-life among nurses in Ethiopia. Therefore, this study aimed to assess the quality of work-life and associated factors among nurses working in Wollega zones in public hospitals, West Ethiopia. Methods: An institutional-based cross-sectional study was conducted on 212 nurses from November to December 2018. The study participants were selected using a simple random sampling method. Data were collected using a self-administered questionnaire and were entered into Epi-data version 3.1 and exported into SPSS version 20.0 for analysis. The binary logistic regression model was conducted to assess the association between the quality of work-life and each independent variable. Multivariable logistic regressions were used to identify factors associated with the quality of work-life and the statistical significance was declared at a p-value of <0.05. Result: A total of 212 nurses were involved in the study (response rate 92.17 %). The majority (61.3 %) of the respondents were males. The mean age of the respondent was 28.36 (SD = 4.1) years. The study revealed that about 108(50.9 %) of nurses had a good quality of work-life. Nurses who have no dependent family were 2.73 times more likely to have a good quality of work-life compared to those who have a dependent family (AOR 2.73, 95 % CI: 1.38, 5.39). Nurses whose monthly income 446–5294 were 2.39times more likely to have a good quality of work-life compared to those who got less than 3653 (AOR 2.39 95 % CI: 1.08, 5.27). Conclusion: Nearly half of the nurses had poor quality of work life. Monthly income and the presence of a dependent family were identified factors associated with quality of work life. Therefore, hospital management, concerned stakeholders, and policymakers are suggested to enhance nurses’ quality of work-life by improving their salary, work environment, and workload.